2012
DOI: 10.1534/genetics.112.140418
|View full text |Cite
|
Sign up to set email alerts
|

Global Population Genetic Structure of Caenorhabditis remanei Reveals Incipient Speciation

Abstract: Mating system transitions dramatically alter the evolutionary trajectories of genomes that can be revealed by contrasts of species with disparate modes of reproduction. For such transitions in Caenorhabditis nematodes, some major causes of genome variation in selfing species have been discerned. And yet, we have only limited understanding of species-wide population genetic processes for their outcrossing relatives, which represent the reproductive state of the progenitors of selfing species. Multilocusmultipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
113
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(125 citation statements)
references
References 52 publications
12
113
0
Order By: Relevance
“…However, additional works concluded that although genetic differentiation is strong in relative terms among the different groups, it remains quite modest in absolute magnitude, further supporting low species-wide polymorphism (F´elix et al, 2013). High gene flow and recombinations were also observed in Caenorhabditis remanei (Dey et al, 2012) except in 1 population of worms obtained from Germany, which can be genetically differentiated from the North American populations, suggesting some degree of isolation by distance. In 1 case, substantial genetic differentiation was observed between a strain collected from China (Caenorhabditis sp.…”
Section: Free-living Nematodesmentioning
confidence: 93%
“…However, additional works concluded that although genetic differentiation is strong in relative terms among the different groups, it remains quite modest in absolute magnitude, further supporting low species-wide polymorphism (F´elix et al, 2013). High gene flow and recombinations were also observed in Caenorhabditis remanei (Dey et al, 2012) except in 1 population of worms obtained from Germany, which can be genetically differentiated from the North American populations, suggesting some degree of isolation by distance. In 1 case, substantial genetic differentiation was observed between a strain collected from China (Caenorhabditis sp.…”
Section: Free-living Nematodesmentioning
confidence: 93%
“…To date, nematodes in general, and Caenorhabditis in particular, have contributed little to these studies [13][14][15][16][17][18][19][20]. However, in recent years, a number of new Caenorhabditis species have been discovered [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, a number of new Caenorhabditis species have been discovered [18,21]. With these new species, four pairwise combinations that yield fertile F1 hybrids have been described [17][18][19]. With these new resources, Caenorhabditis is poised to become an important speciation genetics model system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations